A COMPARATIVE STUDY OF BACK-PROPAGATION ALGORITHMS: LEVENBERG-MARQUART AND BFGS FOR THE FORMATION OF MULTILAYER NEURAL NETWORKS FOR ESTIMATION OF FLUORIDE. (2022) - CHAAL, RACHID EL; ABOUTAFAIL, MOULAY OTHMAN
No abstract available